Investigation of the mutual influence of pores in the weld under thermo-mechanical load - Стрельникова, Елена Александровна; Ковч, Олег Иванович (Eastern-European Journal of Enterprise Technologies, 2015)
The mutual influence of pores in the weld under asymmetric thermo-mechanical load was investigated. The dependence of the geometric characteristics of the chain on the crack opening in the weld was explored. The technique based on the final element method for determining the stress-strain state in the weld around the pores was developed. The technique allows to evaluate the mutual influence of pores on the origin and opening of cracks in space. The technique will allow to increase the life of welds. The feature of the research consists in setting the loads, different in time, depth of plates, length of plates and welds. The analysis of the stress-strain state of the weld at all stages of loading until complete cooling of the design was considered. The research of various load application methods was performed. The reliability of the results was determined using engineering methods. In a pore with a diameter of 3.5 mm, subject to a maximum temperature, stresses are above the allowable σmax=3600 kgs/sm2. In the sites around the pore, the crack opening process will occur. The calculation results show that the pore with a diameter of 3.5 mm in the weld causes cracking, it contradicts the allowable diameter of 4.0mm for such a weld. The importance of the research results lies in investigating the layered asymmetric thermo-mechanical loading. Asymmetric thermo-mechanical loading has led to cracking within the acceptable limits of the geometric parameters of pores.